2014
DOI: 10.1186/1756-3305-7-67
|View full text |Cite
|
Sign up to set email alerts
|

Environmental contamination by canine geohelminths

Abstract: Intestinal nematodes affecting dogs, i.e. roundworms, hookworms and whipworms, have a relevant health-risk impact for animals and, for most of them, for human beings. Both dogs and humans are typically infected by ingesting infective stages, (i.e. larvated eggs or larvae) present in the environment. The existence of a high rate of soil and grass contamination with infective parasitic elements has been demonstrated worldwide in leisure, recreational, public and urban areas, i.e. parks, green areas, bicycle path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
135
0
23

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 170 publications
(162 citation statements)
references
References 67 publications
4
135
0
23
Order By: Relevance
“…The animals from these localities have free movement without restriction and they can contaminate public places with excrements. Problems with uncontrolled and untreated dogs lead to a heavily contaminated environments which under warm climatic conditions could provide good transmission opportunities for zoonotic infections (Won et al, 2008;Lee et al, 2010;Macpherson, 2013). These outcomes are result of depicted cultural and social conditions as well as the lack of fencing and free access to the stray animals.…”
Section: Discussionmentioning
confidence: 99%
“…The animals from these localities have free movement without restriction and they can contaminate public places with excrements. Problems with uncontrolled and untreated dogs lead to a heavily contaminated environments which under warm climatic conditions could provide good transmission opportunities for zoonotic infections (Won et al, 2008;Lee et al, 2010;Macpherson, 2013). These outcomes are result of depicted cultural and social conditions as well as the lack of fencing and free access to the stray animals.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the life mode influence in the infestation level in the dogs from geohelmiths it was observed that the main influence was due to the method used for assessing it. Serological methods have a higher sensitivity than coproscopic methods [2]. Therefore the prevalence of dog's infestation from T. In every season and in every area are collected and analyzed 10 samples of faeces.…”
Section: Resultsmentioning
confidence: 99%
“…Intestinal geohelminths affecting dogs have a relevant health-risk impact on both animals and humans, which are typically infected by ingesting infectious stages: larvated eggs or larvae [2]. The importance of these pathogens is often minimized by veterinarians, human doctors and the general public, although Toxocara canis (T. canis), Ancylostoma spp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…El consejo popular A es urbano con respecto al consejo popular B, que es francamente rural. No obstante, nuestros resultados concuerdan con los obtenidos por Traversa et al (2014) quienes plantean que T. canis y A. caninum son las especies primarias de parásitos que infectan a los perros a nivel mundial. Además aunque los huevos de estos parásitos pueden ser encontrados en diversas áreas urbanas y sitios industrializados, el riesgo de contaminación ambiental es particularmente relevante en comunidades de pobres recursos debido a que los programas extensivos de control de parásitos intestinales están limitados por restricciones financieras.…”
Section: Método De Muestreo Y Tamaño De Muestraunclassified